EFFECTIVENESS OF ADVANCE ORGANIZER MODEL OVER CONVENTIONAL METHODS OF TEACHING OF SCIENCE AT SECONDARY LEVEL - Kapri, Umesh Chandra (International Journal of Research -GRANTHAALAYAH, 2017)
An advance organizer is a very useful tool for teachers to help students in the classroom to understand, retain and remember new learning material. It is a tool used to introduce the lesson topic and illustrate the relationship between what the students are about to learn and the information they have already learned. The most general ideas of a subject are presented first and then progressively differentiated in terms of detail and specificity. Instructional materials are used to integrate new material with previously presented information through comparisons and cross-referencing of new and old ideas. An experimental study was conducted to know the effectiveness of Advance Organizer Model over traditional methods of teaching of science. The findings of the study show that there is significance difference between pre-test and post –test achievement scores of science. Thus, it is concluded that Advance Organizer Model is better in teaching of concepts of science than the conventional methods of teaching of science.